(untitled) (ojs35wn, 2025)
We examine the feasibility of an overland motorised traverse from Pituffik to Greenland’s oldest ice outcrop in Warming Land, North Greenland. We assess a 778 km overland traverse that departs Pituffik via the Nunatarssuaq Take-Off Ramp, which is an alternative to the more frequently used, but more heavily crevassed, Thule Take-Off Ramp. The traverse route includes brief sea ice and primitive road conditions, each c. 4% of the route length, and a lengthy ice sheet segment (c. 92% of the route length). This study outlines challenges for each of these traverse segments, including primitive road conditions and snow cover, seasonality of extreme cold conditions (air temperatures below –30°C), seasonality of surface melting and softening (air temperatures above 0°C), sea-ice thickness and potential ridging hazards, and ice dynamics and potential crevasse hazards. Ongoing work is required for annual vetting of the traverse route to ensure operational safety. The optimal operational window for such a traverse is departing Pituffik in mid-April and returning in mid-May. In comparison to aircraft-supported ice-sheet fieldwork, scientific traverses offer the opportunity for more intensive ground-based science, while significantly reducing carbon emissions. Based on previously reported traverse fuel consumptions, a ground traverse from Pituffik to Warming Land would use 90% less fuel than aircraft supported fieldwork. This assessment underscores the potential for sustainable ground-based access to Greenland’s oldest ice outcrop and other science sites within the region.